Development And Implementation Of Fuzzy Logic Controller For Flow Control Application - Elangeshwaran Pathmanatha, Elangeshwaran (Universiti Teknologi Petronas, 2010)
This paper aims to shed some light on the Development and Implementation of Fuzzy Logic Controller for Flow Control Application. The development will be done onto the PcA Simlxpert Mobile Pilot Plant SE231B-21 Flow Control and Calibration Process (Init. This mobile plant contains flow measurement instruments such as Coriolis, Vortex and Orifice Flow meters. Currently, control and tuning is done via KONICS PID Controller that is mounted on the local control panel